Molecular characterization of Agaricus bisporus strains and their evaluation for production efficiency - B.C. SUMAN, VIJAY KUMAR* and (Indian Phytopathology, 2014)
Ten strains of Agaricus bisporus viz. DMRA-7, DMRA-9, DMRA-14, DMRA-37, DMRA-102, DMRA-103, DMRA-104, DMRA-121, DMRA-122 and U3, procured from different sources were evaluated for production efficiency. DMRA-7, recorded highest average yield of 20 kg per 100 kg compost followed by DMRA-37 (19.17 kg) and DMRA-102 (18.67 kg) based on the average yield of two crops. Strain DMRA-7, in addition to being high yielding also exhibited better morphological quality traits followed by strains DMRA-37, DMRA-102 and U3. The studies on production efficiency have been further supported by the results obtained from RAPD-PCR technology. Studies revealed that eight unique markers viz. OPP-3800, OPP-6700, OPP-6200, OPP-7900, OPP-7700, OPP-9500, OPP-19100 and OPP-19700 have been identified for strain DMRA-7, while only one unique marker OPP-10800 has been identified for control (U3). Sixteen primers amplified 57 RAPD markers, of which 67.92 per cent were polymorphic. Similarity coefficient obtained from RAPD analysis revealed that similarity among all the selected strains ranged between 45 to 76 per cent with an average of 60 per cent.